2008
DOI: 10.1111/j.1365-4632.2008.03595.x
|View full text |Cite
|
Sign up to set email alerts
|

Olmsted syndrome: a case report and review of literature

Abstract: We report a case of an 18-month-old boy with slightly whitened fingernails and toenails since birth. At the age of 100 days, he progressively developed bilateral palmoplantar keratoderma which resulted in painful walking and disabled grasping. Perianal keratotic plaques and perioral hyperkeratotic erythema could also be observed. Both fingernails and toenails were dystrophic. Scalp hairs were sparse, but total alopecia was no present. The histopathologic changes of the biopsy from the inner side of the right f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 26 publications
4
55
1
Order By: Relevance
“…Eight compounds were isolated from the chloroform layer. Compounds 4-30 were identified by detailed comparisons of their spectroscopic data with those in the literature as kaempferol (4), 13) 16) tiliroside (8), 3) quercetin (9), 17) rutin (10), 18) 24) isorhamnetin 3-O-β-d-glucopyranoside (17), 15) gallic acid (18), 25) methyl gallate (19), 26) 4-hydroxybenzoic acid (20), 27) protocatechuic acid (21), 28) methyl brevifolincarboxylate (22), 29) ursolic acid (23), 30) ursolic aldehyde (24), 31) 28-nor-urs-12-ene-3β,17β-diol (25), 32) pomolic acid (26), 33) 2α-hydroxy ursolic acid (27), 33) 23-hydroxy ursolic acid (28), 34) vomifoliol (29), 35) and β-sitosterol (30) 30) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eight compounds were isolated from the chloroform layer. Compounds 4-30 were identified by detailed comparisons of their spectroscopic data with those in the literature as kaempferol (4), 13) 16) tiliroside (8), 3) quercetin (9), 17) rutin (10), 18) 24) isorhamnetin 3-O-β-d-glucopyranoside (17), 15) gallic acid (18), 25) methyl gallate (19), 26) 4-hydroxybenzoic acid (20), 27) protocatechuic acid (21), 28) methyl brevifolincarboxylate (22), 29) ursolic acid (23), 30) ursolic aldehyde (24), 31) 28-nor-urs-12-ene-3β,17β-diol (25), 32) pomolic acid (26), 33) 2α-hydroxy ursolic acid (27), 33) 23-hydroxy ursolic acid (28), 34) vomifoliol (29), 35) and β-sitosterol (30) 30) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…These cytokeratin abnormalities may indicate that the skin involved in Olmsted syndrome retains an immature proliferative profile. Immunohistochemical studies with Ki-67 marker demonstrated that hyperproliferative activity involves the basal and suprabasal keratinocytes in Olmsted syndrome [1, 4]. …”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of the disease depends on clinical features [4, 5]. The two major ones are the symmetrical involvement of keratoderma of the palms and soles and the symmetrical hyperkeratotic plaques around the body orifices.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Histochemical study done in a patient showed more basal and suprabasal keratinocytes of epidermis with immunoreactivity for K 1 67 marker. [9] Another report showed abnormal expression of keratin 5 and 14 in the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is characterized by symmetrical mutilating palmoplantar keratoderma along with periorificial hyperkeratosis (mouth, nose, eyes, genital, anal). [1] We describe two female patients of this syndrome. One of our patients (case 1), had woolly hair and flexion contracture of a digit, in addition to usual features, while the other had pseudoainhum.…”
Section: Introductionmentioning
confidence: 99%